Characterization of a Mouse Model of Emphysema Induced by Multiple Instillations of Low-Dose Elastase - Oliveira, Milena V.; Abreu, Soraia C.; Padilha, Gisele A.; Rocha, Nazareth N.; Maia, Lígia A.; Takiya, Christina M.; Xisto, Debora G.; Suki, Bela; Silva, Pedro L.; Rocco, Patricia R. M. (Frontiers in Physiology, 2016)
Many experimental models have been proposed to study the pathophysiological features of emphysema, as well as to search for new therapeutic approaches for acute or chronically injured lung parenchyma. We aimed to characterize an emphysema model induced by multiple instillations of elastase by tracking the changes in inflammation, remodeling, and cardiac function after each instillation. Forty-eight C57BL/6 mice were randomly assigned across 2 groups. Emphysema (ELA) animals received 1, 2, 3, or 4 intratracheal instillations of pancreatic porcine elastase (PPE, 0.2 IU) with a 1-week interval between them. Controls (C) received saline following the same protocol. Before and after implementation of the protocol, animals underwent echocardiographic analysis. After the first instillation of PPE, the percentage of mononuclear cells in the lung parenchyma was increased compared to C (p = 0.0001). The second instillation resulted in hyperinflated alveoli, increased mean linear intercept, and reduced elastic fiber content in lung parenchyma compared to C (p=0.0197). Following the third instillation, neutrophils and collagen fiber content in alveolar septa and airways were increased, whereas static lung elastance was reduced compared to C (p=0.0094). After the fourth instillation, the percentage of M1 macrophages in lungs; levels of interleukin-1beta, keratinocyte-derived chemokine, hepatocyte growth factor, and vascular endothelial growth factor; and collagen fiber content in the pulmonary vessel wall were increased compared to C (p=0.0096). At this time point, pulmonary arterial hypertension was apparent, with increased diastolic right ventricular wall thickness. In conclusion, the initial phase of emphysema was characterized by lung inflammation with predominance of mononuclear cells, whereas at the late stage, impairment of pulmonary and cardiovascular functions was observed. This model enables analysis of therapies at different time points during controlled progression of emphysema. Accordingly, early interventions could focus on the inflammatory process, while late interventions should focus on restoring cardiorespiratory function.